Le concept de less good idea face aux patrimoines controversés - Monica Heintz (Ateliers d'Anthropologie)
Given the political, intellectual and emotional challenges presented by the sharing of controversial heritage like colonial heritage, the use of artwork has become essential in recent years. Artists are integrated into numerous research projects, collaborating with researchers and collection heads to find forms for transmitting those sensitive materials to diverse audiences. In August 2022, at the Centre for the Less Good Idea in Johannesburg, I took part in a creative residency that explored photographs and moving images captured during Father Aupiais’s mission to Dahomey in 1930, which are part of the Archives of the Planet at the Musée Albert Kahn. On that occasion, based on ten photographs, I wrote and directed a children’s tale, to be performed by three South African artists and a Beninese musician with the help of a Pepper’s ghost setup. Due to the time constraints, only a beta version of this project was able to be put in place and filmed during the residency, with an improvised mise en scène. This experiment could serve as an exemplification of the concept of the less good idea, which was put to the test during the residency, and which seems particularly suitable for the unsolvable equation of the public rendering of traces of colonial relations.